Artaka fish farm community empowerment in karang kepanjen village, trimulyo, sleman, sleman regency - Iswanto Suwarno; Adhianty Nurjanah; Barbara Gunawan; Nia Maharani Raharja; Alfian Ma’arif; Dhiya Uddin Rijalusalam; Rachmad Andri Atmoko; Sashikala Mishra (Peneliti Teknologi Teknik Indonesia, 2021)
Kampung Karang is geographically located at an altitude of 280 meters above sea level. Designated as a green belt area or supporting food needs, the hamlet area has the potential for excellence in the agricultural sector. Kampung Karang has an SME of catfish farming farmers, namely Artaka Fish Farm. Artaka Fish Farm